HER-2 positivity is a high risk of recurrence of stage I gastric cancer - Seonhoo Kim (The Korean Association of Internal Medicine, 2021)
Background/Aims The treatment of gastric cancer remains unsatisfactory. We aimed to investigate the prognostic value of immunohistochemical staining in gastric cancer. Methods We analyzed 505 (279 early staged, 226 advanced-staged) gastric cancer tissues from patients who underwent radical gastric resection between January 2014 and December 2016. Available surgical specimens immunohistochemically stained for p53, epidermal growth factor receptor (EGFR), human EGFR 2 (HER-2), E-cadherin, and Ki-67 were reviewed. We evaluated the association between positivity to various biomarkers and disease recurrence, disease-free survival, lymph node metastasis, and microscopic lymphovascular invasion. Results The median follow-up duration was 32.5 months (range, 7 to 70). Advanced gastric cancer cases showed high Ki-67 expression; other cases showed unremarkable expression. Concerning disease recurrence, lymphatic invasion, and disease-free interval, all biomarkers had no prognostic effects. HER-2-positive stage I gastric cancer tended to occur in old patients and in the upper one-third of the stomach (p = 0.01). HER-2 positivity was significantly correlated with disease recurrence (p = 0.01), lymphatic invasion (p = 0.03), and vascular invasion (p = 0.03) in stage I cases. Conclusions Only HER-2 was associated with the recurrence of stage I gastric cancer. HER-2-positive stage I gastric cancer requires additional therapy despite curative resection.